ATHEROGENIC INDEX OF PLASMA ASSESSMENT AS AN EFFORT TO DETECT THE RISK OF CORONARY HEART DISEASE IN PRODUCTIVE AGE INDIVIDUALS WITH OBESITY IN THE WORKING AREA OF THE SIMPANG SUNGAI DUREN HEALTH CENTER - Puspasari, Anggelia; Maharani, Citra; Halim, Rita; Enis, Rina Nofri; Shafira, Nyimas Natasha Ayu; Tarawifa, Susan (Universitas Jambi, 2025)
Prospective studies indicate that the Atherogenic Index of Plasma (AIP) is a superior marker compared to isolated assessments of triglycerides (TG) and High-Density Lipoprotein (HDL) in predicting Coronary Heart Disease (CHD). Simpang Sungai Duren Community Health Center serves a large population with a high proportion of productive-age and obese individuals. Routine metabolic screening for CHD risk stratification in obese residents has been hindered by limited facilities and healthcare financing systems. This community service initiative aimed to assess AIP for CHD risk stratification in obese individuals. Participants included residents aged 19–64 years with a body mass index (BMI) ≥25 kg/m², no recent lipid-lowering medication use (within 3 months), and an 8–10 hour fasting period. AIP scores (logarithm of TG/HDL ratio) were used to stratify CHD risk. Results were communicated to participants alongside health promotion leaflets. Among 61 participants, AIP-based screening identified 14.8% as high-risk, 26.2% as moderate-risk, and 59% as low-risk for CHD. Modifiable cardiometabolic risk factors in the high-risk group revealed 100% with central obesity and hypertriglyceridemia, and 50% with hypertension and/or low HDL levels. The high-risk cohort exhibited multiple cardiometabolic risks requiring comprehensive management.